SUBTITUSI DEDAK PADI OLEH POD KAKAO YANG DIFERMENTASI Aspergillus niger DALAM RANSUM TERHADAP KARKAS DAN ORGAN DALAM AYAM BROILER (The Substitution of Rice Bran by Cocoa Pod Fermented with Aspergillus niger in Diet on Carcass and Internal Organs of Broil - Harmonista Tarigan (Jurnal Peternakan Integratif, 2013)
ABSTRACT This research aimed to study the rice bran substitution by cocoa pod fermented by Aspergillus niger on  carcass and internal organs of  broiler. The study was conducted at the Laboratory Animal Sciences Faculty of Agriculture University of Sumatera Utara. This study used completely randomized design with 6 treatments and 4 replications. The treatments that used were R0a (commercial feed) and ratio of the substitution rice bran with pod cocoa fermented R0b (100 : 0), R1 (75 : 25), R2 (50 : 50 ), R3 (25 : 75), R4 (0 : 100). The variables were measured consist of slaughter weight, carcass, carcass percentage, relative weight of gizzard, liver, abdominal fat, length of duodenum, jejenum, illeum, caecum. The results show that the rate of substitution of cocoa pod by rice bran gave highly significant different (P<0.01) on decreasing the slaughter weight, carcass weight and carcass percentage, but it gave an increasing in the length of the small intestine and colon. Substitution rate of rice bran by cocoa pod showed non significantly effect (P> 0.05) on relative gizzard weights, relative liver weight and abdominal fat. It can be concluded that the cocoa pod can be used to replace rice bran as much as 50% of the 12% proportion of rice bran in broiler rations Keywords : Cocoa Pods, Aspergilus niger, carcass, internal organs, broiler chickens